Secular Changes of Stature in Rural Children and Adolescents in China, 1985-2010 - Chen, Tian Jiao; Ji, Cheng Ye (Biomedical and environmental sciences, 2014)
Objective To analyze and assess secular change in stature in rural children and adolescents in China from 1985 to 2010. Methods Data were obtained from the 6 rounds of the Chinese National Survey on Student＇s Constitution and Health. The subjects enrolled in the study were children and adolescents aged 7-18 years in rural areas of provincial capitals. Results An overall positive secular trend in stature occurred in rural areas of provincial capitals in China from 1985 to 2010. The overall average increase rates were 3.1 and 2.4 cm/decade for boys and girls, respectively. The total body height increases for grown up boys and girls were 3.6 and 2.3 cm and the increase rates were 1.4 and 0.9 cm/decade, respectively. There were differences in body height increase among eastern, central and western regions. The average body height of the children or adolescents in eastern region was highest, followed by central region and western region. The overall increase rates in central region were highest among the three regions. The difference between eastern/central region and western region was obvious. 〈br〉 Conclusion Positive secular trend in stature of children or adolescents has occurred in rural area of China, and rural boys and girls showed a great potential for continuous growth. More attention should be paid to the differences in children＇s body height between western region and eastern/central region.